Ensnared into Crime: A Preliminary Test of Moffitt's Snares Hypothesis in a National Sample of African Americans - Marcum, Cathy (2010)
The purpose of the present study was to examine the relation between alcohol use and individual differences in the desistance process from criminal behavior during young adulthood. This study used Moffitt's (1993) “snares” hypothesis to posit that alcohol use would slow the desistance process of criminal behavior among African Americans. Using data from the National Longitudinal Survey of the Youth 1997, we conducted dual semiparametric group-based trajectory analysis of criminal behavior and alcohol use among African Americans from ages 16 through 22 (N = 283) using data from the National Longitudinal Survey of the Youth 1997. Results indicate that 3 trajectory groups provided the best representation for the patterns of crime over this period of life. In addition, 4 trajectory groups provided the best representation for the patterns of alcohol use. From our dual-trajectory analysis, we found that African Americans that were desisting slower from crime were using alcohol more often, thus supporting Moffitt's snares hypothesis